1975
DOI: 10.1021/bi00684a032
|View full text |Cite
|
Sign up to set email alerts
|

Ionic and nucleotide requirements for microtubule polymerization in vitro

Abstract: The ionic and nucleotide requirements for the in vitro polymerization of microtubules from purified brain tubulin have been characterized by viscometry. Protein was purified by successive cycles of a temperature dependent assembly-diassembly scheme. Maximal polymerization occurred at a concentration of 0.1 M Pipes (piperazine-N,N'-bis(2-ethanesulfonic acid)); increasing ionic strength by addition of NaCl to samples prepared in lower buffer concentrations did not result in an equivalent level of polymerization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
155
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(173 citation statements)
references
References 24 publications
17
155
1
Order By: Relevance
“…Similarly, it might be expected to alter the functionality of at least a subset of proteins by affecting biomolecular electrostatic interactions. It has long been known that MT polymerization is decreased at high ionic strength in vitro (26,72). This effect would help explain our observation that hypertonicity induces transient MT depolymerization in living cells.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly, it might be expected to alter the functionality of at least a subset of proteins by affecting biomolecular electrostatic interactions. It has long been known that MT polymerization is decreased at high ionic strength in vitro (26,72). This effect would help explain our observation that hypertonicity induces transient MT depolymerization in living cells.…”
Section: Discussionsupporting
confidence: 66%
“…A hallmark feature of hypertonicity is that it induces actin cytoskeleton reorganization (4), and we recently have shown that it also induces fast MT remodeling (13). Because the dynamics of microfilament assembly/disassembly are sensitive to ionic conditions (25,26), a sudden increase in intracellular salt could alter their dynamics and impinge on membrane trafficking. High levels of intracellular salt also could affect membrane trafficking by modulating available energy.…”
Section: Significancementioning
confidence: 99%
“…4A and B). After an initial lag the formation of microtubules increases linearly for [8][9][10] min. The polymerization-dependent GTPase also shows a brief lag, then a linear increase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although investigators have been cautious about proposing a role for GTP in polymerization, the first polymerization of tubulin in vitro from crude extracts of brain contained GTP (5,6). Additional studies in several laboratories (7)(8)(9) with more homogeneous tubulin preparations demonstrated that GTP was required for polymerization and that GTP analogs, guanylylmethylenediphosphate [GMP-P(CH2)P] and guanylylimidodiphosphate [GMP-P(NH)P], were inactive. These results suggested that hydrolysis of the y-phosphate may be necessary for microtubule formation.…”
mentioning
confidence: 99%
“…Low temperature (40) can both prevent and disrupt the tubulin assembled with Gmp(CH2)pp although disruption proceeds much more slowly than when GTP is used. At physiological concentrations (0.5-1 mM) of Mg, the polymerization of tubulin "in vitro" has an essential requirement for nucleoside triphosphates (1,2) and for high molecular weight basic (HMWB) proteins (3). Recently, Arai and Kaziro (4) have assembled microtubules in the presence of guanylyl imidodiphosphate [Gmpp(NH)p] that are relatively resistant to disruption by millimolar concentrations of calcium, conditions that cause extensive disruption of the microtubules assembled in GTP.…”
mentioning
confidence: 99%